Peningkatan Wawasan Karier Siswa SMA melalui Talkshow Berbagi Pengalaman PKL Mahasiswa Fisika FMIPA di SMAIT Daarul ‘Ilmi - Ahmad Faruq Abdurrahman; Nozaline Almahdaly Sandhy; Albert Fhilip Martogi Sibarani; Reza Umami; Orisah Satifah; Muhammad Rifqi Naufal; Elisabeth Br Situmeang (Jurnal Recoms, 2026)
This community service program aimed to broaden high school students’ understanding of career opportunities for physics graduates, who are often associated only with teaching, lecturing, or research. The activity was conducted as an interactive talk show for 23 grade XI students of SMAIT Daarul ‘Ilmi, beginning with a brief introduction to the Physics Department of FMIPA Universitas Lampung. Five physics students then shared their internship experiences at PT Surya Toto Indonesia, PT Bakti Nugraha Yuda Energy, and PTPN I Regional 7 Unit Usaha Pematang Kiwah (PEWA). The method used was participatory presentation followed by question-and-answer sessions after each speaker. During the activity, the students were actively engaged, asked relevant questions, and showed strong interest in the diverse roles of physics graduates in industry. The results indicate that the talk show effectively expanded students’ career insight and helped change their perception that physics is limited to academic professions. This activity can be used as an educational model to introduce broader physics career pathways to senior high school students.